2021
DOI: 10.1186/s13071-020-04514-3
|View full text |Cite
|
Sign up to set email alerts
|

Canine infection with Dirofilaria immitis, Borrelia burgdorferi, Anaplasma spp., and Ehrlichia spp. in the United States, 2013–2019

Abstract: Background Dogs in the US are commonly infected with vector-borne pathogens, including heartworm and tick-borne disease agents. The geographic distribution of both arthropod vectors and the pathogens they transmit continues to expand. Methods To describe the current geographic distribution and prevalence of antigen of Dirofilaria immitis and antibody to Borrelia burgdorferi, Ehrlichia spp., and Anaplasma spp. in dogs, we summarized over 144 million… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 43 publications
7
42
2
3
Order By: Relevance
“…The geographical distribution of canine infection seems to parallel the distribution of HGA in the USA with a positive association of human and canine cases in many states ( 3 , 23 ). Indeed, several studies found the highest prevalence rates of A. phagocytophilum antibodies in dogs from the upper midwest, northeast, and mid-atlantic, which correlate with areas where the highest incidence of human anaplasmosis were reported ( 3 , 4 , 9 , 15 , 22 , 23 ). In addition, the estimated regression coefficient for the endemic risk factor in the contiguous USA model was positive and significant.…”
Section: Epidemiological Role Of Dogsmentioning
confidence: 84%
See 3 more Smart Citations
“…The geographical distribution of canine infection seems to parallel the distribution of HGA in the USA with a positive association of human and canine cases in many states ( 3 , 23 ). Indeed, several studies found the highest prevalence rates of A. phagocytophilum antibodies in dogs from the upper midwest, northeast, and mid-atlantic, which correlate with areas where the highest incidence of human anaplasmosis were reported ( 3 , 4 , 9 , 15 , 22 , 23 ). In addition, the estimated regression coefficient for the endemic risk factor in the contiguous USA model was positive and significant.…”
Section: Epidemiological Role Of Dogsmentioning
confidence: 84%
“…Five countrywide serologic studies showed an overall prevalence of Anaplasma spp. of 1.9 to 4.8% with the highest rates recorded in northeastern regions ( 3 , 9 , 15 , 23 , 119 ). The study that found a prevalence rate of 1.9%, used species-specific peptides to detect canine antibodies to A. phagocytophilum ( 3 ).…”
Section: Distribution and Prevalence Of Anaplasma Phagocytophilummentioning
confidence: 96%
See 2 more Smart Citations
“…Bacterial tick-borne diseases (TBDs) also play an important role in canine medicine, as Ehrlichia spp., Anaplasma spp., Borrelia spp. and Rickettsia conorii are the most common throughout Europe and elsewhere [ 14 , 15 , 16 , 17 ]. Most of the abovementioned pathogens have a zoonotic potential and represent a threat for human health [ 2 , 18 ].…”
Section: Introductionmentioning
confidence: 99%